Retrograde Intrarenal Surgery is equally efficient and safe in patients with different American Society of Anesthesia physical status. (20th April 2016) - Guzel, Ozer; Tuncel, Altug; Balci, Melih; Karakoyunlu, Nihat; Aslan, Yilmaz; Erkan, Anil; Senel, Cagdas
Abstract: Objective To assess the efficacy and safety of Retrograde Intrarenal Surgery to treat renal stones in patients with different American Society of Anesthesia (ASA) physical status.Material and methods We performed a retrospective analysis of 150 patients who underwent Retrograde Intrarenal Surgery for renal stone between October 2013 and December 2014. Patients were categorized into three groups according to their ASA physical status: ASA Class 1 (Group 1, n  = 23), ASA Class 2 (Group 2, n  = 113) and ASA Class 3 (Group 3, n  = 14). We documented and stratified the per-operative and postoperative complications according to modified Satava Classification System and Clavien–Dindo Classification.Results The mean age of the patients was 44 years. The total stone-free rate was 81.2%. According to the groups, the stone-free rate was 75% in Group 1, 82.5% in Group 2, and 83.3% in Group 3 ( p   =    0.340). Per-operative and postoperative complications were recorded in 12% ( n  = 18) and 5.3% ( n  = 8) of the patients. We did not find significant difference in terms of per-operative and postoperative complication rates among patients with different ASA physical status ( p per-operative  = 0.392 and p postoperative  = 0.136).Conclusions Retrograde Intrarenal Surgery is an effective and safe surgery with high stone-free rates and low morbidity in patients with different ASA physical status.